"Trying to Get a Grip": Language Competence and Self-Reported Satisfaction With Social Relationships Three Decades Post-Childhood Traumatic Brain Injury. Issue 5 (September 2016) - Atay, Christina; Ryan, Sarah J.; Lewis, Fiona M.
Abstract : Objective: (1) To investigate outcomes in language competence and self-reported satisfaction with social relationships in long-term survivors of childhood traumatic brain injury (TBI); and (2) to establish whether language competence contributes to self-reported satisfaction with social relationships decades after sustaining childhood TBI. Participants: Twelve females and 8 males aged 30 to 55 (mean = 39.80, standard deviation = 7.54) years who sustained a TBI during childhood and were on average 31 years postinjury (standard deviation = 9.69). An additional 20 participants matched for age, sex, handedness, years of education, and socioeconomic status constituted a control group. Main Measures: Test of Language Competence—Expanded Edition and the Quality of Life in Brain Injury questionnaire. Results: Individuals with a history of childhood TBI performed significantly poorer than their non-injured peers on 2 ( Ambiguous Sentences and Oral Expression: Recreating Sentences ) out of the 4 Test of Language Competence—Expanded Edition subtests used and on the Quality of Life in Brain Injury subscale assessing satisfaction with social relationships. In the TBI group, scores obtained on the Ambiguous Sentences subtest were found to be a significant predictor of satisfaction with social relationships, explaining 25% of the variance observed. Conclusions: The implication of high-level language skills to self-reported satisfaction with social relationships many decades post-childhood TBI suggests that ongoing monitoring of emerging language skills and support throughout the school years and into adulthood may be warranted if adult survivors of childhood TBI are to experience satisfying social relationships. Abstract : Supplemental Digital Content is Available in the Text.